Cytological and Molecular Assessment of Sputum Specimens of the Individuals Suspected to Have Tuberculosis in Wua Settlement in Nasarawa State, Nigeria - Wilson, Utume A; Salvin, Iorkosu T; Funke, Daramola E; Terseer, Aba D; Juliana, Goyang T; Irmiya, Davou G; Adisa, James O; Gamde, Solomon M; Gracious, Bahuyak A (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Approximately 2 million individuals worldwide die of lung tumors each year, accounting for 25% of all cancer-related deaths. Nigeria has the sixth highest rate of tuberculosis worldwide and the highest incidence in Africa. Objective: This study aimed to evaluate cytological and molecular parameters of sputum specimens collected from individuals suspected to have tuberculosis in Wua Settlement in Nasarawa State, Nigeria. Methods: The cross-sectional study was carried out from June to October of 2024. A structured questionnaire was used to collect demographic characteristics, knowledge and awareness, and behavioural factors of the respondents. One hundred and eleven subjects participated in this research. Sputum specimens were collected from each participant using sterile sputum containers. Papanicolaou’s stain, GeneXpert, and direct Gram of the sputum were conducted. Results: Of the 111 participants, 94(84.7%) were farmers by occupation. About risk factors, 22(19.8%) reported being smokers, with smoking duration ranging between 1 and 20 years, while 50(45%) admitted to consuming alcohol. 93(88.3%) participants had normal sputum smears, 17(15.5%) showed signs of inflammation, and 1(0.9%) had a premalignant condition. No case of MTB was detected. Other findings included Gram-positive cocci arranged in chains in 86(77.5%) participants, in clusters in 17(15.5%), Gram-positive diplococci in 2(1.8%), and Gram-negative bacilli in 6(5.4%). Conclusion: Cytological and molecular assessment techniques played a vital role in sputum analysed for determination of the bacterial infections’ distribution and percentage distribution of cellular abnormalities in the study participants. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 243-251